Application analysis of adsorption refrigeration system for solar and data center waste heat utilization. (15th January 2021) - Pan, Quanwen; Peng, Jiajie; Wang, Ruzhu
Abstract: Since the energy and environment issues, adsorption refrigeration technology has raised the great attention and interest by worldwide researchers and scholars, because it can efficiently use low-grade heat and its refrigerants are natural. Among the numerous working pairs of adsorption refrigeration, silica gel-water is most suitable for massive applications in solar and waste heat field, as its developed technology and low driving temperature. In this paper, application analysis of adsorption refrigeration system for solar and data center waste heat utilization and economic evaluation, based on investment of main components, operation cost and payback period, is done. For the study of solar cooling application, a validated mathematical model of silica gel-water adsorption chiller is used. For very low temperature waste heat (up to 60 °C) recovery of data center, feasibility of silica gel-water adsorption chiller has been analyzed by previous experimental study. Through the investigation, payback period of solar cooling application using adsorption chiller is too long to get any economic benefit, based on the real weather conditions of Shanghai. Data center waste heat recovery by adsorption chiller has very short payback period and this application has greater economic potential and brighter prospect in the future than solar cooling application.